PENDAMPINGAN DAN SOSIALISASI ALUR PENDAFTARAN DI RUMAH SAKIT DESA LABUAN, KECAMATAN MOUTONG, KABUPATEN PARIGI MOUTONG - Farlin Musa; Muhammad Akmar (LPPM Universitas Bina Mandiri Gorontalo, 2025)
The hospital registration process is a crucial initial step in providing effective and efficient healthcare services. However, rural communities, particularly the elderly, still experience limited understanding of the registration process due to limited knowledge, education, and access to information. This study aims to improve public understanding of the hospital registration process through educational activities led by health cadres. The method used was direct community education, providing material and guidance related to the hospital registration process. The results showed an increase in public understanding of the hospital registration process, which impacted patient readiness to access healthcare services appropriately. A well-understood registration process contributes to reduced administrative barriers, service efficiency, and improved patient experience. Thus, education on the hospital registration process plays a crucial role in supporting optimal and sustainable healthcare services.